NATO and evidence-based military and disaster medicine: case for Vigorous Warrior Live Exercise Series - Quinn, John; Bencko, Vladimír; Bongartz, Alexander V; Stoeva, Preslava; Atanasoska Arsov, Adrijana; De Porzi, Stefano; Bohoněk, Miloš; Ti, Ronald; Taylor, Jack; Mitchell, John; Reinhard, Veronika; Májovský, Peter; et al. (Central European Journal of Public Health, 2020)
The North Atlantic Treaty Organization (NATO) is the premier and only security alliance uniting 30 countries and growing with many partner states in the provision of collective security and against threats posed by conflict and natural disasters. Security of countries and communities is increasingly threatened by a broad spectrum of unconventional types of war and disease threats - from hybrid and asymmetric to multi-domain and peer-to-peer/near-peer conflict. The NATO Centre of Excellence for Military Medicine (MILMED COE) is the centre of gravity for medical best practices and promotion of medical doctrine across the NATO alliance. Disaster medicine is multidisciplinary and in NATO, multinational, requiring best practices that are driven by data and evidence to prevent death on the battlefield and prepare for future conflicts. "Vigorous Warrior" is a live military and disaster medicine exercise series using both civilian and military actors across all sectors of health focused on health security and identifying lessons learned to ready the alliance for future threats. In this brief report, we make the case that the Vigorous Warrior exercise exposes gaps, highlights challenges and generates an evidence base to make NATO military medicine systems more robust, more efficient and in provision of best medical practices. We specifically argue that clinical data capture must be duplicated and continuous across the alliance to ensure evidence-based medicine stays current in NATO military medical doctrine.
Keywords: Disaster Medicine; Military Medicine; Military Personnel; medicína katastrof; vojenské lékařství; ozbrojené síly; lidé; cvičení; Humans; Exercise